Self-Esteem, Depression, Anxiety and Quality of Life in Patients with Melasma Living in a Sunny Mediterranean Area: Results from a Prospective Cross-Sectional Study - Eftychia Platsidaki; Vasiliki Efstathiou; Vasiliki Markantoni; Anargyros Kouris; Georgios Kontochristopoulos; Electra Nikolaidou; Dimitrios Rigopoulos; Alexandros Stratigos; Stamatios Gregoriou (Adis, Springer Healthcare, 2023)
Abstract Introduction Melasma is a common acquired disorder of hyperpigmentation and has a significant effect on quality of life. The aim of this prospective cross-sectional study was to assess the effect of melasma on depression, social anxiety and self-esteem in the Greek population. Methods The study included a total of 254 participants: 127 patients with melasma and an equal sample of healthy controls. Both participant groups completed the following psychometric measures: the Hospital Anxiety and Depression Scale (HADS) to assess anxiety and depression and Rosenberg's Self-esteem Scale (RSES) for self-esteem. Furthermore, in patients with melasma, quality of life was assessed using Melasma Quality of Life (MELASQoL). Results Melasma patients (7.47 ± 4.53) presented statistically significantly higher anxiety compared to healthy controls (6.06 ± 3.59, p = 0.006), while no differences emerged with regard to depression or self-esteem. It is important to note that the difference regarding anxiety remained significant (b = 1.25, p = 0.003) even after adjusting for age, depression and self-esteem. A higher disease severity (MASI) correlated statistically significantly with longer disease duration (r = 0.24, p < 0.001), higher depression (r = 0.28, p = 0.002), and a more impaired health-related quality of life (MelasQol; r = 0.29, p < 0.001). Notably, a more impaired health-related quality of life was also correlated with higher depression (r = 0.19, p = 0.027) and lower self-esteem (r = − 0.31, p < 0.001). Conclusion The results of this study highlight the importance of evaluating quality of life, anxiety and depression in patients with melasma. The therapeutic approach should not be based solely on clinical findings; it should also include an evaluation of the patient's psychological aspects. Dermatologists can further improve their patient care by being supportive or requesting psychological intervention when needed, resulting in better compliance with treatment and an improved social and psychological status.